Permeable pavements for storm water control incorporating nano clay. Issue 1 (1st January 2021) - Ayobami, Busari; Julius, Ndambuki; Emmanuel, Sadiku; Snyman, Jacques; Williams, Kupolati; Olugbenga, Amu; Damilola, Ayangbayi; Olayemi, Fadipe Olusola; Loto, Roland Tolulope
Abstract: Stormwater affects the economic situation of the environment, changes the land use, which also affects the ecosystem. Consequently, this affects the pavement condition of the road and lead to both structural and functional pavement defects. In a bid to proffer solution to the harmful effects of stormwater and reduce the cost of pavement construction in track with sustainability, this research utilized nano clay in the development of permeable concrete. The nano clay was used as a partial replacement for cement. It was dehydroxylated at 720°C; the characterization and particle geometry was done using the XRF equipment. The de-hydroxylated nano clay was used as a partial replacement for cement at 5, 10, 15, 20 and 25%. Correspondingly, six samples of concrete were developed. The mechanical properties (compressive and flexural strength) of the permeable concrete was assessed at 3, 7, 14, 21 and 28 days. Additionally, the porosity of the concrete was determined using Archimedes principle. The result of the research showed that using nano clay replacement at 15% gave a flexural strength of 4.01MPa. This is lower than the required specification of 4.27Mpa—4.5MPa for pavement construction at 28 days and 4.5Mpa and above for airfield pavement. The porosity test using Archimedes principle showed a satisfactory result. This proves the efficiency of the concrete for stormwater control. Therefore, this concrete is recommended for use in the design and construction of low axle or low trafficked road for stormwater control and aquifer recharge based on the flexural strength.